2022
DOI: 10.1186/s40729-022-00413-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival of implant-based oral rehabilitation following maxillofacial reconstruction with vascularized bone flap

Abstract: Aim The aim of the study was to assess the 5-year cumulative survival rate of implant-based dental rehabilitation following maxillofacial reconstruction with a vascularized bone flap and to investigate the potential risk factors which might influence the survival rate. Materials and methods A retrospective cohort study was designed. Inclusion criteria involved 18 years old or above patients with the availability of clinical and radiological data an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…The primary oncologic diagnosis was oral squamous cell carcinoma in most studies (66.7%), followed by adenoid cystic carcinoma 8,[18][19][20] and other malignant tumors/carcinomas of the head and neck. [21][22][23][24] Primary reconstruction, defined as FFF reconstruction occurring during the tumor resection surgery, was the only reconstructive method performed in 14 studies. Secondary reconstruction, defined as the FFF reconstruction in a separate surgery after the first ablative surgery, was the sole reconstruction method performed in 5 studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary oncologic diagnosis was oral squamous cell carcinoma in most studies (66.7%), followed by adenoid cystic carcinoma 8,[18][19][20] and other malignant tumors/carcinomas of the head and neck. [21][22][23][24] Primary reconstruction, defined as FFF reconstruction occurring during the tumor resection surgery, was the only reconstructive method performed in 14 studies. Secondary reconstruction, defined as the FFF reconstruction in a separate surgery after the first ablative surgery, was the sole reconstruction method performed in 5 studies.…”
Section: Resultsmentioning
confidence: 99%
“…19,[25][26][27][28][29][30] Supplemental Table 2, Supplemental Digital Content 1, http://links.lww.com/SCS/G5 provides information about the implants and RTX treatment. Eight studies described implants placed in both native bone and the flap, 8,18,[20][21][22]29,31,32 Neckel and colleagues had all implants placed in the irradiated native bone, and the remaining 11 studies described implants placed only in the fibula. Fifteen studies included patients with maxillary and mandibular implants, with the remaining 5 presenting only mandibular implants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are comparable to those published by several authors, who registered an overall implant survival of 93.5% on average, with a range of percentages between 83 and 97% from 1 to 5 years after placement [ 1 , 21 , 34 49 ], and a mean 5-year survival rate of 91% [ 50 ]. Lower values of 5-year implant survival (81% [ 51 ], 85.6% [ 52 ], and 87.2% [ 53 ]) were reported in studies which underlined recurrence of tumor, soft tissue proliferation, and infection as main factors involved in implant failure. On the other hand, higher percentages of 97.2% [ 33 ] and 98% [ 48 ] were reported after a mean follow-up of even 8 years after implant loading.…”
Section: Discussionmentioning
confidence: 99%
“…Lei et al reported a 93.2% cumulative survival rate of implants placed in bone flaps, with a longest follow-up of 12.9 years; 10 Wei et al reported 5-, 10-, and 20-year implant survival rates of 90.1%, 83.1%, and 69.3%, respectively; 11 Gerardo et al reported 1-, 5-, and 10-year implant survival rates of 97.2%, 86.5%, and 79.3%, respectively; 12 Sameh et al reported 1-and 11-yearcumulative survival rates of 93% and 78%, respectively;13 and Hongyang et al reported 1-, 2-and 5-year cumulative survival rates of 96%, 87%, and 81%, respectively 14. In this study, only 7 out of 100 implants failed, with 5-and 10-year implant survival rates of 95.0% and 91.5%, respectively.…”
mentioning
confidence: 99%